The Look of Lyric: Greek Song and the Visual Studies in Archaic and Classical Greek Song, vol. 1 - Cazzato, Vanessa; Lardinois, André (Mnemosyne, Supplements, 2016)
The Look of Lyric: Greek Song and the Visual addresses the varied modes of interaction between ancient Greek lyric poetry and the visual arts as well as more general notions of visuality. Readership: Students and scholars of ancient Greek literary and visual culture, especially those interested in Greek lyric poetry.